2015
DOI: 10.1097/wnr.0000000000000363
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of (−)-epigallocatechin-3-gallate in thrombin-induced neuronal cell apoptosis and JNK-MAPK activation

Abstract: (−)-Epigallocatechin-3-gallate (EGCG), the major polyphenolic component of green tea, has anti-inflammatory and antioxidant properties and provides neuroprotection against central nervous system diseases. Yet, it is not known whether EGCG may be neuroprotective against intracerebral hemorrhage. In this study, we used a simplified in-vitro model of thrombin neurotoxicity to test whether EGCG provides neuroprotection against thrombin-associated toxicity. Exposure of primary cortical neurons to thrombin (100 U/ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…Lai et al [ 30 ] reported that using the JNK inhibitor SP600125, or using SP600125 and z-VAD together could significantly suppress the neuronal apoptosis in heroin-induced spongiform leukoencephalopathy. He et al ’s study [ 31 ] showed that (−)-Epigallocatechin-3-gallate (EGCG) could significantly prevent apoptosis by suppressing JNK phosphorylation, and that the JNK inhibitor SP600125 could reduce thrombin-induced caspase 3 activation and apoptosis after ICH. Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al [ 30 ] reported that using the JNK inhibitor SP600125, or using SP600125 and z-VAD together could significantly suppress the neuronal apoptosis in heroin-induced spongiform leukoencephalopathy. He et al ’s study [ 31 ] showed that (−)-Epigallocatechin-3-gallate (EGCG) could significantly prevent apoptosis by suppressing JNK phosphorylation, and that the JNK inhibitor SP600125 could reduce thrombin-induced caspase 3 activation and apoptosis after ICH. Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase exists in cells as an inactive zymogen form, and becomes an active fragment following proteolytic processing, and thus is used in the investigation of cell apoptosis (17). In neuronal apoptosis induced by various stimuli, caspase acts as a modulating agent (18). With increasing doses of H 2 O 2 , the expression of caspase-9 is increased (19).…”
Section: Discussionmentioning
confidence: 99%
“…Sesamin, a lignan of sesame seed oil, is a promising natural product as a novel therapeutic strategy based on the regulation of microglial activities via inhibition of inducible NO synthase (iNOS) protein expression and accompanied by the activated p44/42 MAPK pathway in ICH [ 133 ]. Other natural plant extracts can be used as natural antioxidants, including resveratrol [ 134 ], astaxanthin [ 135 ], baicalein [ 136 ], astragaloside [ 137 ], proanthocyanidin [ 138 ], (−)-epigallocatechin-3-gallate [ 139 ], and apple polyphenol [ 97 ]. Studies in ICH animal models have shown that treatment using these extracts can exhibit neuroprotective effects by inhibiting oxidative stress, upregulating antioxidant levels, and reducing SBI after ICH.…”
Section: Antioxidant Therapy After Ichmentioning
confidence: 99%